2017
DOI: 10.5811/westjem.2017.1.31223
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-Performed Bedside Ultrasound in Improving Diagnostic Accuracy in Patients Presenting to the ED with Acute Dyspnea

Abstract: IntroductionDiagnosing acute dyspnea is a critical action performed by emergency physicians (EP). It has been shown that ultrasound (US) can be incorporated into the work-up of the dyspneic patient; but there is little data demonstrating its effect on decision-making. We sought to examine the impact of a bedside, clinician-performed cardiopulmonary US protocol on the clinical impression of EPs evaluating dyspneic patients, and to measure the change in physician confidence with the leading diagnosis before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…We found that our standardized ultrasound strategy did not significantly change the physician’s diagnosis, although we observed a modest increase in their diagnostic confidence. This finding is in contrast to that of Papanagnou et al [20] who reported a moderate increase in diagnostic confidence and some changes in management. Consistent with the lack of a change in diagnosis, we found that un-blinding the ultrasound data did not change therapy or disposition decisions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that our standardized ultrasound strategy did not significantly change the physician’s diagnosis, although we observed a modest increase in their diagnostic confidence. This finding is in contrast to that of Papanagnou et al [20] who reported a moderate increase in diagnostic confidence and some changes in management. Consistent with the lack of a change in diagnosis, we found that un-blinding the ultrasound data did not change therapy or disposition decisions.…”
Section: Discussioncontrasting
confidence: 99%
“…They reported similar mean±standard deviation times of 24± 10 and 186±72 minutes for ultrasound and standard of care diagnostic time, respectively. Finally, both Mantuani et al [19] and Papanagnou et al [20] found that the most common final diagnoses in patients presenting to the ED with acute dyspnea were heart failure, airway disease, and pneumonia, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Experts’ comments [ 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ] Inflammatory lesions are categorized as parenchymatous (consolidation with an irregular marginal contour, dynamic air bronchogram visible within the consolidation and/or the air trapping sign), vascular (normal flow pattern in CD and PD options) and pleural (pleural effusion). This description of lesions does not apply to bronchopneumonia.…”
Section: Recommendationsmentioning
confidence: 99%
“…Despite evidence that the B line artefact is strongly associated with pulmonary oedema, quantification of B lines appears to be more nuanced than originally proposed . Studies are limited by convenience sampling and the lack of an accessible clinical gold standard with most studies resorting to post hoc expert opinion.…”
Section: Introductionmentioning
confidence: 99%
“…With two important exceptions, most are prospective observational trials. LUS performs less well when performed by non‐expert sonologists on a broad cohort …”
Section: Introductionmentioning
confidence: 99%